Is good teaching culturally responsive? - Madalina Tanase (Journal of Pedagogical Research, 2020)
Demographic data show an increasingly diverse student population in all urban settings. This contrasts with the teacher force, which is predominately middle class, female, monolingual, and of European ancestry. This discrepancy adds complexity to an already complex profession. To bridge this cultural gap, researchers advocate for a change in the teaching paradigm, in which teachers understand the relationship between students' culture and learning. This paradigm is called Culturally Responsive Teaching. The participants of this study were twenty-two secondary mathematics and science teachers. The researcher analyzed whether some of the strategies used in mathematics and science urban classrooms were student-centered as well as culturally responsive. Results show that teachers used a variety of student-centered strategies, such as discovery learning, centers and group work, and games. Similarly, the teachers incorporated their students' culture into their mathematics and science classrooms, by including their students' interests in the lessons, exposing students to similar role models, and using real-life examples that students found relatable.